PELATIHAN PENGELOLAAN FINANSIAL USAHA MIKRO KEWIRAUSAHAAN PESANTREN UMMUL QURO - Novita, Dina; supatmin, supatmin; Nurita, Endang (LAP4B, 2026)
The Community Service Program (PKM) implements comprehensive financial management training for entrepreneurial micro-enterprises at the Ummul Quro Islamic Boarding School, responding to the global challenge of financial literacy reflected in UNESCO data that only one-third of the global adult population is adequately financially literate. This study uses a qualitative approach with a participatory training method involving 45 participants of students and ustadz during an intensive period of three months. The results of the training showed a significant improvement in the understanding of financial management, business bookkeeping, and financial planning with a satisfaction rate of 87% of participants. This program contributes to increasing the institutional capacity of Islamic boarding schools in developing economic independence based on Islamic values, while strengthening the position of universities in ranking social impact through the implementation of Sustainable Development Goals (SDGs), especially SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth).